Huanglongbing (HLB; citrus greening) Leaf and Fruit Symptom Identification - Jamie D. Burrow; Megan M. Dewdney (EDIS, 2019)
Huanglongbing (HLB), commonly known as citrus greening, is a bacterial disease that affects all citrus varieties. This 2-page fact sheet is a minor revision that describes the leaf and fruit symptoms of HLB. Written by Jamie D. Burrow and Megan M. Dewdney, and published by the Plant Pathology Department, July 2019.